Predictors of mortality among injecting and non-injecting HIV-negative drug users in northern Thailand - Vu Minh Quan (2018)
Aims: To estimate mortality rates among HIV-negative injecting drug users (IDUs) and non-injecting drug users (non-IDUs), and to assess predictors for mortality among the IDUs. Design: Prospective cohort study in northern Thailand with 2-year follow-up. Setting: IDUs and non-IDUs who were admitted for detoxification treatment for opiate or amphetamine dependence in a regional drug treatment center were screened. After discharge, HIV-negative individuals were followed-up in the community. Participants: A total of 821 HIV-negative drug users [346 IDUs (42%) and 475 non-IDUs, median age = 32; 51% were ethnic minorities]. Measurements: All-cause mortality. Findings: There were 33 deaths over 1360 person-years of follow-up. The all-cause mortality rate was 39 per 1000 person-years among IDUs [standardized mortality ratio (SMR) = 13.9], and was 14 per 1000 person-years among non-IDUs (SMR = 4.4). Among male IDUs, the hazards for all-cause deaths were ethnic minority status [adjusted hazard ratio (HR) = 2.9, 95% CI = 1.2-7.2], incident HIV infection (HR = 2.8, 95% CI = 1.1-7.7) and longer duration of drug injection (HR = 1.07, 95% CI = 1.01-1.14). Conclusions: The mortality among IDUs is high. Being from an ethnic minority, recent HIV acquisition, and a greater number of years of drug injection are predictors of mortality among the IDUs in this region. © 2007 The Authors.